2015
DOI: 10.1002/srin.201500259
|View full text |Cite
|
Sign up to set email alerts
|

Study of a New Mold Flux for Heat‐Resistant Steel Containing Cerium Continuous Casting

Abstract: New mold fluxes with CaO–Al2O3–Li2O–CeO2 system are proposed for heat‐resistant steel continuous casting. The fundamental properties are investigated systematically. It is found that the appropriate content of CeO2 is determined to be ≈10 wt%, the melting temperature did not change much with increasing CeO2 content, which indicates that the mold fluxes could show steady smelting properties after continuously absorbing inclusions containing cerium in the continuous casting process. After adding CeO2, the precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…There are some studies on the CaO-Al 2 O 3 -based mold fluxes and CaO-SiO 2 -based mold fluxes with different RE x O y contents. Some researchers 14,17) suggested that the CaO-Al 2 O 3 -based mold fluxes with low reactivity can be used in the casting process of the rare earth alloy heating resisting steels. CeO 2 showed good properties of decreasing the viscosity.…”
Section: Effects Of Ceo 2 On Melting Temperature Viscosity and Strumentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies on the CaO-Al 2 O 3 -based mold fluxes and CaO-SiO 2 -based mold fluxes with different RE x O y contents. Some researchers 14,17) suggested that the CaO-Al 2 O 3 -based mold fluxes with low reactivity can be used in the casting process of the rare earth alloy heating resisting steels. CeO 2 showed good properties of decreasing the viscosity.…”
Section: Effects Of Ceo 2 On Melting Temperature Viscosity and Strumentioning
confidence: 99%
“…Then it increased to 16.58% after the second furnace. 11) It was also reported that the rare earth oxides have a great effect on the melting temperature, viscosity, [12][13][14] structure [15][16][17][18][19] and crystallization 18,20) of mold fluxes. Specifically, the melting temperature and the viscosity property have direct influence on the lubrication between the solidified shell and the casting mold, [21][22][23] even the quality of the casting block.…”
Section: Introductionmentioning
confidence: 99%
“…The results are shown in the following discussions. [24][25][26] show that Li ion, which has the minimum ionic radius, has just one positive charge, implying Li + could freely move in the space of [AlO 4 ]-tetrahedrons and Li + ions have the priority to compensate the highly-polymerized [AlO 4 ]-tetrahedrons. Moreover, ionic bonds between cations and anions also exist in the molten slag, such as Ca-O ionic bond and Ce-O ionic bond.…”
Section: Crystallization Process Of the Mold Fluxesmentioning
confidence: 99%
“…In order to solve the abovementioned problems, researchers have proposed the use of low-reactive CaO-Al 2 O 3based mold uxes with SiO 2 ≤ 10 wt% (as shown in region B in Figure 1) for steel grades with serious slag-steel reaction [13][14][15][16]. However, the high activity of CaO in the mold uxes tends to generate high melting point CaTiO 3 with TiO 2 , as shown in Eq.…”
Section: Introductionmentioning
confidence: 99%